Prevalence of Burnout Syndrome and Fear of COVID-19 among Adolescent University Students - Raimundo Aguayo-Estremera; Gustavo R. Cañadas; Luis Albendín-García; Elena Ortega-Campos; Tania Ariza; Carolina S. Monsalve-Reyes; Emilia Inmaculada De la Fuente-Solana (Children, 2023)
This study aimed to estimate the prevalence of burnout syndrome in adolescents entering university studies, to detect differences in burnout levels, personality factors and fear of coronavirus in a pandemic context due to COVID-19. A cross-sectional predictive study was performed with a sample that comprised 134 individuals in their first year of a Psychology degree at Spanish universities. The Maslach Burnout Inventory Student Survey, the NEO Five-Factor Inventory and the Fear of COVID-19 Scale were applied. The prevalence of burnout is estimated according to three methods: Maslach and Jackson’s severity classification, Golembiewski’s phase model and Maslach et al.’s profile model. The estimates show significant differences. The results indicated that between 9 and 21% of students were at risk of developing burnout. On the other hand, students who reported having suffered psychological consequences of the pandemic showed greater emotional exhaustion, neuroticism and fear of COVID-19, and a lower level of personal accomplishment than those who did not suffer such consequences. Neuroticism was the only significant predictor for all burnout dimensions, and fear of COVID-19 did not contribute to any of them.